Computer-delivered cognitive-behavioural treatments for obsessive compulsive disorder: preliminary meta-analysis of randomized and non-randomized effectiveness trials. (December 2014) - Pozza, Andrea; Andersson, Gerhard; Antonelli, Paolo; Dèttore, Davide
Abstract: Cognitive behavioural treatments (CBTs) are well-established for obsessive compulsive disorder (OCD). However, few patients receive CBT, due to factors like geographical limitations, perceived stigmatization, and lack of CBT services. Some evidence suggests that computer-delivered cognitive-behavioural treatments (CCBTs) could be an effective strategy to improve patients' access to CBT. To date a meta-analysis on effectiveness of CCBTs for OCD has not been conducted. The present study used meta-analytical techniques to summarize evidence on CCBTs for OCD on OCD and depression symptom outcomes at post-treatment and follow-up. A meta-analysis was conducted according to PRISMA guidelines. Treatments were classified as CCBTs if including evidence-based cognitive-behavioural components for OCD (psychoeducation, exposure and response prevention, cognitive restructuring), delivered through devices like computers, palmtops, telephone-interactive voice-response systems, CD-ROMS, and cell phones. Studies were included if they used validated outcomes for OCD. Eight studies met inclusion criteria ( n = 392). A large effect favouring CCBTs over control conditions was found for OCD symptoms at post-treatment ( d = 0.82, p = 0.001), but not for depression symptom outcomes ( d = 0.15, p = 0.20). Theoretical implications and directions for research are discussed. A larger number of randomized controlled trials is required.